2016
DOI: 10.1080/03019233.2016.1251749
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion evolution after calcium addition in Ti-bearing Al-kill steel

Abstract: In current article, experiments with different calcium addition were carried out in an Al 2 O 3 crucible at 1873 K to investigate the variation of inclusion in Ti-bearing Al-kill Steel. It was found that calcium significantly influenced the morphology, composition distribution and size of oxide inclusions in Ti-bearing Al-kill Steel. Liquid oxide inclusions were modified promptly after calcium addition. Meanwhile, calcium could also modify solid titanium aluminate inclusions to spherical ones similarly, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Based on the published papers , the industrial experimental research results with calcium treatment from 2011 to 2021 are summarized as shown in Table 1. According to Table 1, thermodynamic calculation and SEM-EDS analysis are widely used to study the formation and modification mechanism of inclusions in different steel grades, the evolution law of compositions, sizes, numbers and morphology characteristics of the different inclusions after calcium treatment in different steel grades [1][2][3]6,8,10,[12][13][14][21][22][23][24][25][26], and the optimization and improvement of calcium treatment process [4,5,9,20,29], as well as the mechanism reducing nozzle nodulation and the degree of tundish stopper erosion with calcium treatment [27,28]. The modification and local concentration of inclusions, rate-controlling step of inclusion modification and change of inclusion compositions with different reaction times in calcium treatment steel can be studied in combination with numerical simulation and kinetic models [7,11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the published papers , the industrial experimental research results with calcium treatment from 2011 to 2021 are summarized as shown in Table 1. According to Table 1, thermodynamic calculation and SEM-EDS analysis are widely used to study the formation and modification mechanism of inclusions in different steel grades, the evolution law of compositions, sizes, numbers and morphology characteristics of the different inclusions after calcium treatment in different steel grades [1][2][3]6,8,10,[12][13][14][21][22][23][24][25][26], and the optimization and improvement of calcium treatment process [4,5,9,20,29], as well as the mechanism reducing nozzle nodulation and the degree of tundish stopper erosion with calcium treatment [27,28]. The modification and local concentration of inclusions, rate-controlling step of inclusion modification and change of inclusion compositions with different reaction times in calcium treatment steel can be studied in combination with numerical simulation and kinetic models [7,11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these existing problems, numerous researchers [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have studied the modification of Al 2 O 3 and spinel-type inclusions. Calcium treatment is the most commonly used modification method.…”
Section: Introductionmentioning
confidence: 99%
“…Ca is one of the most common modifiers for inclusions especially for Al 2 O 3 and MgO•Al 2 O 3 in the steelmaking process [25][26][27][28]. For one thing, Ca treatment partially or fully modified angular Al 2 O 3 and MgO•Al 2 O 3 into spherical Ca-Al or Ca-Mg-Al-O complex oxides, which reduces the probability of nozzle clogging and improves the properties of final products [27][28][29]. For another, the Ca-containing inclusions are prone to work as heterogeneous nucleation sites of MnS during the cooling process due to their high sulphides capacities [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Ca is one of the most common modifiers for inclusions especially for Al 2 O 3 and MgO·Al 2 O 3 in the steelmaking process [2528]. For one thing, Ca treatment partially or fully modified angular Al 2 O 3 and MgO·Al 2 O 3 into spherical Ca–Al or Ca–Mg–Al–O complex oxides, which reduces the probability of nozzle clogging and improves the properties of final products [2729].…”
Section: Introductionmentioning
confidence: 99%